Toward a smart skin: Harnessing cuticle biosynthesis for crop adaptation to drought, salinity, temperature, and ultraviolet stress - Liu, Lang; Wang, Xiaoyu; Chang, Cheng (Frontiers in Plant Science, 2022)
Drought, salinity, extreme temperatures and ultraviolet radiation are major environmental factors that adversely affect plant growth and crop production. As a protective shield covering the outer epidermal cell wall of plant aerial organs, the cuticle is mainly composed of cutin matrix impregnated and sealed with cuticular waxes, and greatly contributes to the plant adaption to environmental stresses. Past decades have seen considerable progress in uncovering the molecular mechanism of plant cutin and cuticular wax biosynthesis, as well as their important roles in plant stress adaptation, which provides a new direction to drive strategies for stress-resilient crop breeding. In this review, we highlighted the recent advances in cuticle biosynthesis in plant adaptation to drought, salinity, extreme temperatures and ultraviolet radiation stress, and discussed the current status and future directions in harnessing cuticle biosynthesis for crop improvement.